Etika Desain Antarmuka: Praktik Manipulatif (Dark Patterns) pada Platform Digital - Jihaan Adzanishaafiya Anwar; Evy Nurmiati (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
On contemporary digital platforms, user interface (UI) design plays a dual role: it eases how services are used while also nudging the way people act. Design choices that are deliberately built to deceive, pressure, or steer users toward options favoring providers rather than the users themselves are what scholars label dark patterns. This article frames such patterns as an ethical concern within interface design and interprets their consequences through the lens of professional ethics. Methodologically, it relies on a systematic literature review (SLR) spanning 20 peer-reviewed works released between 2021 and 2026, compiled from well-regarded databases as well as national journals and filtered using predefined inclusion and exclusion criteria. The evidence indicates that dark patterns are widespread, surfacing across most e-commerce, mobile, and social-media services, and typically taking the shape of forced action, obstruction, sneaking, urgency, and confirmshaming. Ethically, they conflict with the foundational values of the IT profession, namely respect for user autonomy, honesty, transparency, and the duty to prevent harm. The study argues that curbing dark patterns demands a blend of ethical design (bright patterns), responsive regulation, and stronger digital literacy, thereby reinforcing professional design ethics within Indonesia's digital ecosystem.